First assessment of ectoparasite prevalence in Apennine populations of Eurasian red squirrel: does habitat fragmentation affect parasite presence?. Issue 5 (3rd September 2022) - Franchini, Marcello; Mazza, Giuseppe; Mori, Emiliano
Abstract : Although habitat fragmentation is widely reported to affect species survival and distribution, its effect in terms of host-parasite interactions in small mammal communities is poorly studied yet. Using information collected from carcasses of 34 road-kill and two preyed-upon individuals, we present the first comprehensive study dealing with the relationship between habitat fragmentation and the presence of different ectoparasite species infecting a small Sciurus vulgaris population inhabiting the Apennine ridge. We predicted that the probability to find individuals infested by parasites would be lower in highly fragmented areas because of the trade-off effects over both mammal and ectoparasite communities. Our findings showed that the most frequent ectoparasites were the squirrel fleas Ceratophyllus sciurorum and hard ticks Ixodes ricinus . Males showed higher presence of ectoparasites than females, probably because of different behaviour in space use and higher hormone levels, which may compromise host's resistance to infection. As to the relationship with habitat fragmentation, we did not find support that individuals in highly fragmented areas would be less susceptible to C. sciurorum infestation because of lower red squirrel relative density. The presence of highly suitable habitat patches in fragmented habitats may have favoured the presence of squirrels, hence promoting C. sciurorum transmission among specimens. Similarly, we did not find support that habitat fragmentation would have reduced the likelihood of generalist ectoparasites transmission among squirrels. This finding may be explained by the increasing tolerance of generalist ectoparasites towards habitat fragmentation because of the presence of species (e.g., roe deer Capreolus capreolus ) able to better exploit ecotonal areas. We believe that our research provides interesting preliminary results on ectoparasites infesting red squirrels in the Apennine area, and of the potential impact which habitat fragmentation may have on them. Nevertheless, the effect of habitat fragmentation over parasite communities is still poorly considered, and further researches are needed.